Una revisión bibliográfica de la perspectiva de los recursos (RBV) en la investigación desarrollada en España (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2016)
The purpose of this paper is to analyse the role-played in our country by the Resource-Based View of the Firm (RBV) in the area of business economics. Firstly, we make an introduction to the fundamentals of the RBV and then, we study the influence of this theory among the Spanish scholars, revising the main works carried out.
Keywords: Competitive Advantage; Resources; Capabilities; RBV